Diversity of Australian Ornixolinae (Lepidoptera: Gracillariidae) with taxonomic and nomenclatural acts within the related taxa (Acrocercopinae and Gracillariinae) based on the evidence of museomics, bionomics, and mitogenomics - de Prins, Jurate; Hartley, Diana; Sruoga, Virginijus; Nicholls, James; Wallace, Jesse; Zwick, Andreas (Zootaxa, 2025)
Advances in genomics enable the inclusion of historic collection specimens in phylogenetic analyses for the delimitation of natural groups. We capitalise on these developments to generate data from independent sources like mitochondrial genomes, morphology and bionomics. Using leaf-mining moths as model organisms, we address the evolutionary problems in the Australian biogeographical realm, from learning about the morphological traits and associated bionomics to revealing principles of the relationship between plants and insects based on genetic studies. We use museum specimens and mitochondrial genomics to associate century-old and often in bad condition primary type specimens with more recent accessions at the Australian National Insect Collection, Canberra, Australia, adding detailed morphological descriptions and bionomics like host records to otherwise relatively bare names. Genomic data yield well-resolved phylogenies, while morphology and bionomics improve visual evidence and practical biological knowledge. All three datasets fine-tune the taxonomy of the global Gracillariidae and the Australian members of the subfamily Ornixolinae in particular. In the present study, we demonstrated that some Australian species which were considered to belong to Ornixolinae in fact, should be classified as part of Acrocercopinae or Gracillariinae. We use holistic analyses to learn about species and species-group boundaries, assisting in species and higher taxa delimitation and classification. Novelties presented in this article: 9 new genera: Bridella De Prins, Sruoga & Zwick, gen. n.; Crotona De Prins, Sruoga & Zwick, gen. n.; Dondavisia De Prins, Sruoga & Zwick, gen. n.; Kallia De Prins, Sruoga & Zwick, gen. n.; Murwillumbah De Prins, Sruoga & Zwick, gen. n.; Ornica De Prins, Sruoga & Zwick, gen. n.; Polka De Prins, Sruoga & Zwick, gen. n.; Ponga De Prins, Sruoga & Zwick, gen. n.; Toowoomba De Prins, Sruoga & Zwick, gen. n. 38 new species: Bridella doo De Prins, Sruoga & Zwick, sp. nov.; Crotona kakadu De Prins, Sruoga & Zwick, sp. nov.; Cuphodes calycanthae De Prins, Sruoga & Zwick, sp. nov.; Cuphodes drypette De Prins, Sruoga & Zwick, sp. nov., Cuphodes leucoptera De Prins, Sruoga & Zwick, sp. nov.; Diphtheroptila auris De Prins, Sruoga & Zwick, sp. nov.; Diphtheroptila breynella De Prins, Sruoga & Zwick, sp. nov.; Diphtheroptila cairna De Prins, Sruoga & Zwick, sp. nov.; Diphtheroptila cornuta De Prins, Sruoga & Zwick, sp. nov.; Diphtheroptila crotonella, De Prins, Sruoga & Zwick, sp. nov.; Diphtheroptila djabu De Prins, Sruoga & Zwick, sp. nov.; Diphtheroptila glochidia De Prins, Sruoga & Zwick, sp. nov.; Diphtheroptila glochidiella De Prins, Sruoga & Zwick, sp. nov.; Diphtheroptila nix De Prins, Sruoga & Zwick, sp. nov.; Diphtheroptila virosae De Prins, Sruoga & Zwick, sp. nov.; Dondavisia digitata De Prins, Sruoga & Zwick, sp. nov.; Epicephala breyniphaga De Prins, Sruoga & Zwick, sp. nov.; Epicephala doddi De Prins, Sruoga & Zwick, sp. nov.; Epicephala dunkensis De Prins, Sruoga & Zwick, sp. nov.; Epicephala philippa De Prins, Sruoga & Zwick, sp. nov.; Epicephala sydnea De Prins, Sruoga & Zwick, sp. nov.; Epicephala xerocarpa, De Prins, Sruoga & Zwick, sp. nov.; Gibbovalva lambertiae De Prins, Sruoga & Zwick, sp. nov.; Gibbovalva lomatiae De Prins, Sruoga & Zwick, sp. nov.; Kallia myopora De Prins, Sruoga & Zwick, sp. nov.; Liocrobyla kuranda De Prins, Sruoga & Zwick, sp. nov.; Liocrobyla pinnatae De Prins, Sruoga & Zwick, sp. nov.; Parectopa acaciella De Prins, Sruoga & Zwick, sp. nov.; Parectopa braidella De Prins, Sruoga & Zwick, sp. nov.; Parectopa melanoxyla De Prins, Sruoga & Zwick, sp. nov.; Polka commoni De Prins, Sruoga & Zwick, sp. nov.; Polydema eubenangee De Prins, Sruoga & Zwick, sp. nov.; Polydema macaranga De Prins, Sruoga & Zwick, sp. nov.; Polydema mallota De Prins, Sruoga & Zwick, sp. nov.; Polydema virgula De Prins, Sruoga & Zwick, sp. nov.; Ponga pinna De Prins, Sruoga & Zwick, sp. nov.; Stomphastis dhileepani De Prins, Sruoga & Zwick, sp. nov.; Toowoomba toowoomba De Prins, Sruoga & Zwick, sp. nov. 2 new synonymisation acts: Cyphosticha Meyrick, 1907 syn. n. = Cuphodes Meyrick, 1897; Conopomorpha heliopla (Meyrick, 1907) syn. n. = Polysoma eumetalla (Meyrick, 1880). 14 new combinations: Cuphodes acrolitha (Meyrick, 1908a), comb. n. (= Cyphosticha acrolitha); Cuphodes albomarginata (Stainton, 1862), comb. n. (= Gracilaria albomarginata); Cuphodes callimacha (Meyrick, 1920), comb. n. (= Acrocercops callimacha); Cuphodes microta (Turner, 1894), comb. n. (= Gracillaria microta); Cuphodes pandoxa (Turner, 1913), comb. n. (= Cyphosticha pandoxa); Cuphodes pterocola (Meyrick, 1914b), comb. n. (= Cyphosticha pterocola); Cuphodes pyrochroma (Turner, 1894), comb. n. (= Gracillaria pyrochroma); Gibbovalva zaplaca (Meyrick, 1907), comb. n. (= Conopomorpha zaplaca); Kallia murtfeldtella (Busck, 1904), comb. n. (= Gracillaria murtfeldtella); Murwillumbah panconita (Turner, 1913), comb. n. (= Cyphosticha panconita); Ornica australis (Turner, 1896), comb. n. (= Ornix australis); Parectopa epimicta (Turner, 1913), comb. n. (= Acrocercops epimicta); Polysoma heliopla (Meyrick, 1907), comb. n. (= Conopomorpha heliopla); Toowoomba dialeuca (Turner, 1940), comb. n. (= Cyphosticha dialeuca). Neotype designation: Gracillaria heteropsis Lower, 1894. 19 Lectotype designations: Conopomorpha chionochtha Meyrick, 1907; Conopomorpha habrodes Meyrick, 1907; Conopomorpha zaplaca Meyrick, 1907; Coriscium ochridorsellum Meyrick, 1880; Cuphodes didymosticha Turner, 1940; Cuphodes habrophanes Turner, 1940; Cuphodes maculosa Turner, 1940; Cyphosticha dialeuca Turner, 1940; Epicephala colymbetella Meyrick, 1880; Epicephala invita Meyrick, 1912; Epicephala stephanephora Turner, 1923; Epicephala zalosticha Turner, 1940; Gracillaria albistriatella Turner, 1894; Gracillaria cramerella Snellen, 1904; Gracillaria mnesicala Meyrick, 1880; Gracillaria pyrochroma Turner, 1894; Ornix trigonophora Turner, 1900; Phrixosceles lithographa Meyrick, 1912; Ornix australis Turner, 1896. New distribution records for Australia: Diphtheroptila oxyloga (Meyrick, 1928a); Stomphastis labyrinthica (Meyrick, 1918), genera Liocrobyla Meyrick, 1916b, Polydema Vári, 1961. New hostplants: Ebenaceae: Diospyros calycantha O. Schwarz, a new host plant record for Gracillariidae. Euphorbiaceae: Mallotus polyadenos F. Muell., M. paniculatus Müll. Arg., Macaranga involucrata Baill. for the genus Polydema Vári, 1961. Fabaceae: Acacia dealbata Link, A. melanoxylon R. Br., A. pycnantha Benth. for the genus Polysoma Vári, 1961; A. trinervata Sieber ex DC., A. mangium Willd., for Ornica australis (Turner, 1896); Flemingia parviflora Benth, F. trifloliastrum Domin, Pongamia pinnata (L.) Pierre, Pongamia sp. for the genus Liocrobyla; Neptunia major (Benth.) Windler for the genus Neurostrota Ely, 1918. Phyllanthaceae: Breynia cernua (Poir.) Müll, Breynia oblongifolia (Müll. Arg.) Müll. Arg. Breynia sp., Flueggea virosa (Roxb. ex Willd.) Royle, Glochidion philippicum (Cav.) C.B. Rob for the genus Diphtheroptila Vári, 1961; Breynia oblongifolia (Müll. Arg.) Müll. Arg, Glochidion philippicum (Cav.) C.B. Rob., G. xerocarpus O. Schwarz for the genus Epicephala Meyrick, 1880. Putranjivaceae: Drypetes deplanchei (Brongn. & Gris) Merr., new host plant record and new host plant family for Gracillariidae.